Concurrent Validity of The Expanded Cutting Alignment Scoring Tool (E-CAST) - Lauren Butler; Alexa Martinez; Ashley Erdman; Dai Sugimoto; Alex Loewen; Eryn Milian; Charles Wyatt; Kristin Hayden; Amie DeVerna; Kirsten Tulchin-Francis; Sophia Ulman (International Journal of Sports Physical Therapy)
# Background